2016
DOI: 10.1007/978-94-024-0890-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Yersinia pestis and the Epidemiology of Plague

Abstract: This chapter summarizes information about the natural foci of plague in the world. We describe the location, main hosts, and vectors of Yersinia pestis. The ecological features of the hosts and vectors of plague are listed, including predators - birds and mammals and their role in the epizootic. The epizootic process in plague and the factors affecting the dynamics of epizootic activity of natural foci of Y. pestis are described in detail. The mathematical models of the epizootic process in plague and predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…For example; the Enterobacteriaceae and Vibrionaceae, which possess an Lpp, Pal and OmpA (Fig. A) have evolved to occupy a dynamic range of niches with species able to survive transitioning between animal digestive systems and mucosa, soil and fresh or saline water (Johnson, ; Dubyanskiy and Yeszhanov, ; Jang et al ., ). Each species must be able to continue to grow and divide in changing osmotic, pH and temperature conditions from host to environment, and back again in some cases.…”
Section: Passive Outer Membrane Constriction By Simple Tethering?mentioning
confidence: 99%
“…For example; the Enterobacteriaceae and Vibrionaceae, which possess an Lpp, Pal and OmpA (Fig. A) have evolved to occupy a dynamic range of niches with species able to survive transitioning between animal digestive systems and mucosa, soil and fresh or saline water (Johnson, ; Dubyanskiy and Yeszhanov, ; Jang et al ., ). Each species must be able to continue to grow and divide in changing osmotic, pH and temperature conditions from host to environment, and back again in some cases.…”
Section: Passive Outer Membrane Constriction By Simple Tethering?mentioning
confidence: 99%
“…Within the subgenus Plocopsylla , Plocopsylla ( P .) hector is reportedly a vector of plague in Ecuador (Lewis, ), parasitizing rodents of the genus Thomasomys belonging to the subfamily Sigmodontinae (Dubyanskiy & Yeszhanov, ). In the present study, all species identified as hosts of the new flea species are sigmodontine rodents.…”
Section: Discussionmentioning
confidence: 99%
“…In Bolivia and Peru, plague is endemic in the Andean region and several rodents (Sigmodontine and Murinae) have been identified as reservoirs (Ruiz, 2001;Álvaro et al, 2013;Schneider et al, 2014). Within the subgenus Plocopsylla, Plocopsylla (P.) hector is reportedly a vector of plague in Ecuador (Lewis, 1993), parasitizing rodents of the genus Thomasomys belonging to the subfamily Sigmodontinae (Dubyanskiy & Yeszhanov, 2016). In the present study, all species identified as hosts of the new flea species are sigmodontine rodents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vladimir presented the forecasting model, which was developed based on non-homogeneous sequential pattern recognition procedures used previously for plague prediction (Dubyanskiy and Yeszhanov, 2016; Dubyansky et al, 1992; Gubler, 1978). Monthly values of climatic factors (e.g., average temperature, relative air humidity, rainfall, snow cover depth, atmospheric pressure) and epidemiological data (e.g., number of cases in the past year, numbers of localities with reported CCHF activity) are used as predictors.…”
Section: Meeting Sessionsmentioning
confidence: 99%